1999
DOI: 10.1063/1.124151
|View full text |Cite
|
Sign up to set email alerts
|

Electron mobility exceeding 104 cm2/V s in an AlGaN–GaN heterostructure grown on a sapphire substrate

Abstract: High-quality AlGaN/GaN undoped single heterostructures (SH) with different Al contents have been grown on sapphire substrates. The magnetotransport investigation was performed on these samples at a low temperature. The observation of Shubnikov–de Hass oscillations in the magnetic fields below 3 T and the integer quantum Hall effect confirmed the existence of the two-dimensional electron gas (2DEG) at the AlGaN/GaN interface. The Al0.18Ga0.82N/GaN SH shows a Hall mobility of 10 300 cm2/V s at a carrier sheet de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 8 publications
3
28
0
4
Order By: Relevance
“…[7][8][9]29,35,36 The increments in mobility due to photoexcitation at a fixed temperature can be attributed to the increased electron mean energy with an increasing carrier density in the 2DEG channel, which leads to an improved screening and thereby reduced scattering between the 2DEG electrons with the ionized donor impurities. 24,29 The 9 These results show that there are considerable compressive strains that exist in our GaN layers due to the mismatch between the epilayers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9]29,35,36 The increments in mobility due to photoexcitation at a fixed temperature can be attributed to the increased electron mean energy with an increasing carrier density in the 2DEG channel, which leads to an improved screening and thereby reduced scattering between the 2DEG electrons with the ionized donor impurities. 24,29 The 9 These results show that there are considerable compressive strains that exist in our GaN layers due to the mismatch between the epilayers.…”
Section: Resultsmentioning
confidence: 99%
“…5,6 High-quality AlGaN/GaN heterostructures have been shown to contain two-dimensional electron gas ͑2DEG͒, which has attracted special interest due to its potential applications in high mobility transistors operating at high power and high temperature levels. [7][8][9][10] The device structures are usually grown on highly lattice-mismatched substrates, such as sapphire, 11 SiC, 12 or Si. 13 It still remains difficult to obtain a high-quality GaN epilayer because of the large lattice mismatch ͑ϳ14% for sapphire and ϳ3.5% for SiC͒ as well as the difference in the thermal expansion coefficients ͑ϳ80% for sapphire and ϳ3.2% for SiC͒ between the GaN film and sapphire and SiC substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The undoped GaN/AlGaN heterostructure used in this work (J401) was grown by MOCVD on a sapphire substrate [5]. A 2 mm undoped GaN layer was grown on a 25 nm GaN buffer layer and capped with 120 nm Al x Ga 1Àx N (x ¼ 0:18).…”
Section: Methodsmentioning
confidence: 99%
“…According to the calculation of Leung et al [19] , when the dislocation density is in the range of N DIS = 10 8 -10 10 cm −2 , only 10%-50% of the energy states will be occupied (f DIS = 0.1-0.5), so f DIS = 0.3 is adopted in the calculation. In some undoped AlGaN/GaN structures with low Al content, it is observed that the low temperature 2DEG mobility increases with Al content [20] . The DIS scattering may be one of the principal factors underlying the phenomena.…”
Section: Resultsmentioning
confidence: 98%